Heat-conducting and wave-absorbing multifunctional TPU (thermoplastic polyurethane) composite film as well as preparation method and application thereof

The V2O5@NaV6O15@PPy nanofiber and TPU composite film was prepared through liquid phase dissolution-recrystallization-redox polymerization process, which solved the problems of thickness, unevenness and poor compatibility of the integrated thermal conductivity-absorbing material, and achieved high The strength, low density, broadband and lightweight thermal-absorbing multifunctional film is suitable for harsh environments, and simplifies process and reduces costs.

CN119264642APending Publication Date: 2025-01-07ZHEJIANG NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411449829.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing thermal-absorbing integrated materials have problems such as thick thickness, unbalanced uniformity, heavy mass, poor compatibility with thermal conductivity and wave absorption performance. The process is complex and costly, making it difficult to achieve simplicity, controllable structure and low filling ratio. , industrial solutions with excellent performance.

Method used

V2O5@NaV6O15@PPy nanofibers were prepared by liquid phase dissolution-recrystallization-redox polymerization process, and a multifunctional TPU composite film was prepared by evaporating solvent film formation process to achieve both thermal conductivity and wave absorption performance.

Benefits of technology

It has obtained a high-strength, self-cleaning, low-density, broadband and lightweight thermal-absorbing multifunctional film, with excellent thermal conductivity and microwave absorption performance, suitable for harsh environments, simple process and safe raw materials, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264642A_ABST
    Figure CN119264642A_ABST
Patent Text Reader

Abstract

The invention discloses a heat-conducting and wave-absorbing multifunctional TPU (thermoplastic polyurethane) composite film as well as a preparation method and application thereof, and belongs to the technical field of application of heat-conducting and wave-absorbing integrated materials. The preparation method comprises the following steps: by taking V2O5-coated NaV6O15-coated PPy core-shell structure nanofibers as a heat-conducting and wave-absorbing multifunctional filler and 1, 4-dioxane as a solvent, uniformly mixing with a TPU matrix according to a series of proportions, and evaporating the solvent to obtain the heat-conducting and wave-absorbing multifunctional V2O5-coated NaV6O15-coated PPy / TPU composite film. The preparation method disclosed by the invention is simple to operate, the product morphology is novel, the characteristics of harsh reaction conditions, difficulty in regulation and control of the morphology of the reaction product, poor experiment repeatability and the like in the previous preparation process are overcome, and the obtained composite film has the characteristics of high strength, good flexibility, excellent self-cleaning, high heat conductivity and broadband light microwave absorption; and the method has good industrial application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of heat conduction and wave absorption, relates to a heat conduction and wave absorption integrated material and its heat conduction and wave absorption application, and specifically discloses a self-cleaning, high-strength, heat conduction and wave absorption multifunctional TPU composite film and its preparation method and application. Background Art

[0002] The development of electronic information technology has put forward high requirements on the thermal conductivity and anti-electromagnetic interference performance of products. The integration and high power of devices make the heating phenomenon of electronic equipment more serious. Thermal conductive-wave absorbing integrated materials can effectively solve the above problems due to their effective improvement of electromagnetic wave attenuation and high thermal conductivity. However, most of the thermal conductive and wave absorbing products at home and abroad are separate, and related research is also independent research on thermal conductive and wave absorbing materials. There are few reports on thermal conductive-wave absorbing integrated materials. So far, most of the thermal conductive-wave absorbing integrated products on the market simply physically mix high thermal conductivity and wave absorbing powders to achieve the purpose of taking into account both thermal conductivity and wave absorption. However, such products have many defects such as thick thickness, uneven uniformity, and heavy weight. At the same time, from the perspective of mechanism, the compatibility between thermal conductivity and wave absorbing performance is poor. Therefore, it is crucial to find a balance between wave absorbing and thermal conductivity.

[0003] Conductive polypyrrole (PPy) has excellent electrical conductivity due to the presence of a large number of delocalized electrons in its π-conjugated structure. In its internal heat conduction, there is not only phonon transmission caused by lattice vibration, but also electron transmission caused by free electrons. In the field of wave absorption, due to the conductivity of conductive polymers, the conductivity loss and dielectric constant can be greatly improved, which can greatly improve impedance matching and electromagnetic wave attenuation characteristics. Therefore, polypyrrole has great application potential in the field of thermal conduction and wave absorption.

[0004] Microscopic morphology and defects have a significant impact on the thermal conductivity and wave absorption properties of materials. In the field of wave absorption, one-dimensional materials can significantly improve the orientation polarization of materials, effectively improve impedance matching and electromagnetic wave attenuation performance; in the field of thermal conductivity, one-dimensional materials can effectively form a thermal network to improve thermal conductivity efficiency. Defects can enhance defect polarization and enhance electromagnetic wave loss in the field of wave absorption; while in the field of thermal conductivity, defects will cause phonons to generate phonon scattering in the lattice, reducing thermal conductivity.

[0005] A Chinese invention patent (CN118027667A) discloses a method for preparing and applying iron silicon aluminum @ metal oxide powder @ polypyrrole core-shell microspheres. Although the product obtained by this method has certain thermal conductivity and wave absorption properties, the morphology of the synthesized product is irregularly spherical. As a thermal conductive filler, it has the defects of too high filling ratio and heavy weight. A Chinese invention patent (CN115246994B) discloses a method for synthesizing and applying a two-dimensional sheet graphene @ Al2O3 @ PPy thermal conductive wave absorbing integrated flexible material. Although the spiral PPy is synthesized by chemical oxidation polymerization, the graphene and Al2O3 are physically mixed and stirred to form a heterogeneous material, thereby achieving the purpose of taking into account both thermal conductivity and wave absorption, the thermal conductive wave absorbing integrated flexible material has a high filling ratio (≥55%) and high cost.

[0006] Therefore, how to develop a thermal conductive-wave absorbing integrated material with simple process, controllable structure, low filling ratio, excellent performance, low cost and industrializability has become an urgent problem to be solved in research in this field. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide a heat-conducting-wave-absorbing multifunctional TPU composite film and its preparation method and application in view of the problems existing in the prior art, and specifically discloses a self-cleaning, high-strength, heat-conducting-wave-absorbing multifunctional V2O5@NaV6O composite film with simple process, rich yield and industrialization. 15 @PPy nanofiber / TPU film.

[0008] In order to achieve the above object, the technical solution of the present invention is as follows:

[0009] The first technical purpose of the present invention is to provide a heat-conducting and wave-absorbing multifunctional TPU composite film, wherein the multifunctional TPU composite film is V2O5@NaV6O 15 @PPy nanofiber / TPU film is prepared by dispersing a heat-conducting and wave-absorbing multifunctional filler and a thermoplastic polyurethane elastomer (TPU) matrix into an organic solvent in a certain proportion, and forming a film by evaporating the solvent; the heat-conducting and wave-absorbing multifunctional filler is V2O5@NaV6O 15 @PPy nanofibers have a one-dimensional core-shell structure with a length of 23 to 80 μm and a diameter of 48.7 to 265.9 nm; and the mass percentage of the thermal conductive and wave absorbing multifunctional filler in the TPU matrix is ​​1 to 7%.

[0010] The second technical purpose of the present invention is to provide a method for preparing the thermally conductive and wave-absorbing multifunctional TPU composite film as described above, wherein the multifunctional TPU composite film is prepared by evaporating a solvent to form a film, and specifically comprises the following steps:

[0011] (1) Add a certain amount of TPU particles to an organic solvent under an oil bath condition of 75-85°C and stir for 3-6 hours to obtain solution A;

[0012] (2) The thermal conductive and wave absorbing multifunctional filler (V2O5@NaV6O 15 @PPy nanofibers) are added to the solution A in step (1) in a certain proportion, ultrasonically dispersed for 10 to 30 minutes, and vigorously stirred for 3 to 4 hours to obtain a thermal conductive and wave absorbing slurry;

[0013] (3) pouring the thermal conductive and microwave absorbing slurry described in step (2) into a mold, evacuating the mold at room temperature, and removing bubbles for 3 to 5 minutes;

[0014] (4) placing the mold after removing the bubbles in step (3) in a 60° C. oven to evaporate the solvent for 10 to 20 hours to obtain the thermal conductive and wave absorbing multifunctional TPU composite film.

[0015] Preferably, the solvent in step (1) is 1,4-dioxane, and the concentration of TPU is 0.083-0.125 g / mL.

[0016] Preferably, in step (2), V2O5@NaV6O 15 @The mass percentage of PPy thermal conductive and wave absorbing powder in the TPU matrix is ​​1-7%.

[0017] Preferably, the thermal conductive and wave absorbing multifunctional filler, namely V2O5@NaV6O 15 @PPy nanofibers are prepared by liquid phase dissolution-recrystallization-redox polymerization process; the V2O5@NaV6O 15 @PPy nanofibers are flat one-dimensional core-shell nanofiber structures, and the V2O5@NaV6O 15 The aspect ratio of @PPy nanofibers is 88-489, the density is 0.1353-0.4250 g / cm, and the conductivity is 0.0189-0.0240 S / m.

[0018] Furthermore, the liquid phase dissolution-recrystallization-redox polymerization process is as follows: V2O5 powder and NaCl are mixed with deionized water in a certain proportion and stirred at 75°C for 24 hours to obtain V2O5 fiber; then, Py monomer is added to the fiber as a template and oxidant, and the Py monomer is polymerized in situ on the fiber surface to obtain V2O5@NaV6O 15 @PPy nanofibers are finally washed to remove soluble salts, thereby obtaining the thermal conductive and wave absorbing multifunctional filler.

[0019] Preferably, the mass ratio of V2O5, NaCl and deionized water is 0.009:0.007:1, and the mass ratio of Py to V2O5@NaV6O15 The molar ratio is 5 to 15:1.

[0020] It should be noted that the present invention discloses V2O5@NaV6O prepared by liquid phase dissolution-recrystallization-redox polymerization process. 15 @PPy nanofibers not only have novel structures and thermal conductivity and wave absorption mechanisms, but can also regulate V2O5@NaV6O by changing the PPy loading amount. 15 Defects and conductivity of @PPy nanofibers, V2O5@NaV6O 15 @PPy nanofibers have a length of 23-80 μm, a diameter of 48.7-265.9 nm, a conductivity of 0.0189-0.0240 S / m, and an oxygen defect content of 6.91%-19.73%. 15 @PPy filler is a one-dimensional core-shell structure with a suitable number of defects and strong anisotropy. In the field of thermal conduction, as a filler, it can effectively control phonon scattering and interconnected thermal conduction networks; in the field of wave absorption, it can effectively improve defect polarization, orientation polarization and interface polarization, and has great potential in the fields of thermal conduction and wave absorption.

[0021] In addition, the V2O5@NaV6O prepared by the present invention 15 @PPy nanofibers have excellent thermal conductivity and microwave absorption properties, with a thermal conductivity of 2.69 to 3.56 W / (m·K), a maximum effective bandwidth of 7.52 to 9.84 GHz with a reflectivity of less than or equal to -10 dB, a maximum absorption of -22.3 to -40.2 dB, and a thickness of 2.8 to 3.6 mm.

[0022] The third technical purpose of the present invention is to provide a V2O5@NaV6O 15 @Application of PPy nanofiber / TPU film in microwave absorption and thermal conductivity.

[0023] Specifically, the method for preparing the heat-conducting and wave-absorbing multifunctional TPU composite film disclosed in the present invention comprises the following steps:

[0024] (1) Weigh a certain mass of salt and vanadium pentoxide powder, dissolve them in a certain volume of deionized water, then heat at a certain temperature and stir magnetically for a period of time to form V2O5@NaV6O by liquid phase dissolution-recrystallization. 15 Nanofiber suspension;

[0025] (2) adding a certain volume of Py monomer to the suspension, and subjecting it to chemical oxidation polymerization reaction at a certain temperature for a certain time to obtain a crude product;

[0026] (3) The crude product is filtered several times and then dried to finally obtain the V2O5@NaV6O 15 @PPy nanofibers;

[0027] (4) Under oil bath conditions at a certain temperature, a certain mass of TPU particles is added to a certain volume of solvent and stirred for 3 to 6 hours to obtain solution A;

[0028] (5) A certain mass of thermal conductive and wave absorbing multifunctional filler (V2O5@NaV6O 15 @PPy nanofibers) were added to solution A and stirred for a period of time at a certain temperature to obtain a thermal conductive-wave absorbing slurry;

[0029] (6) Pour the thermal conductive and microwave absorbing slurry into a mold, vacuum dry it for a certain period of time, dry it at a certain temperature, and then remove the mold to obtain the thermal conductive and microwave absorbing multifunctional TPU composite film.

[0030] By adopting the above technical solution, the beneficial effects of the present invention are as follows:

[0031] The preparation method disclosed in the present invention is simple to operate and has novel product morphology and mechanism, which overcomes the characteristics of harsh reaction conditions and low yield in previous preparation processes and has good industrial application potential.

[0032] Preferably, the salt in step (1) is NaCl with a mass of 0.5697 g; the volume of deionized water is 85 mL, the mass of V2O5 is 0.7280 g, the heating temperature is 75°C, and the stirring time is 24 h.

[0033] Preferably, the reaction temperature in step (2) is 0°C and the reaction time is 12h.

[0034] Preferably, the mass of the TPU particles in step (4) is 5 g, the volume of 1,4-dioxane is 40-60 mL, the dissolution temperature is 85° C., and the dissolution time is 6 h.

[0035] Preferably, the mass of step (5) is one of 0.0505, 0.1546, 0.2632 and 0.3763 ​​g, the temperature is 85° C., and the stirring time is 1 h.

[0036] Preferably, the time of step (6) is 10 to 20 hours, and the drying temperature is 60°C.

[0037] It can be seen from the above technical solutions that, compared with the prior art, the present invention provides a heat-conducting and wave-absorbing multifunctional TPU composite film and a preparation method and application thereof, which have the following excellent effects:

[0038] 1) The present invention uses the synthesized V2O5 fiber precursor as a template and oxidant, Py monomer as a raw material, TPU as a matrix, and a liquid phase dissolution-recrystallization-redox polymerization process to prepare V2O5@NaV6O with a one-dimensional core-shell morphology. 15 @PPy thermal conductive fillers and sheets, with aspect ratios of 88.9 to 489, and the V2O5@NaV6O 15 @Defects, conductivity and interface of PPy. The PPy shell can effectively improve the interfacial compatibility between the conductive filler and the matrix, thereby improving the mechanical and hydrophobic properties.

[0039] 2) V2O5@NaV6O prepared by the present invention 15 @PPy has the characteristics of light weight, low density, high conductivity, strong anisotropy, etc. Its shell surface can be loaded with magnetic metal particles, further improving its application in the field of wave absorption.

[0040] 3) V2O5@NaV6O 15 The preparation method of @PPy material is simple, the raw materials are safe, the products are abundant, the chemical stability is strong, it is green and environmentally friendly, it can be industrialized, has low requirements for instrument precision, and has good application potential.

[0041] 4) V2O5@NaV6O 15 @PPy nanofiber / TPU film has many functions such as high strength, good flexibility, excellent self-cleaning, high thermal conductivity and broadband lightweight microwave absorption, and can be used in harsh environments such as rainy days or humidity. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0043] Figure 1 to Figure 3 They are respectively the phase and morphology of the product obtained in Example 1 of the present invention measured under XRD, EDX and scanning electron microscope.

[0044] Figures 4 to 6 They are respectively the phase and morphology of the product obtained in Example 4 of the present invention measured under XRD, EDX and scanning electron microscope.

[0045] Figure 7 to Figure 9 They are respectively the phase and morphology of the product obtained in Example 5 of the present invention measured under XRD, EDX and scanning electron microscope.

[0046] Figure 10 to Figure 12 They are respectively the phase and morphology of the product obtained in Example 6 of the present invention measured under XRD, EDX and scanning electron microscope. DETAILED DESCRIPTION

[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] The embodiment of the present invention discloses a V2O5@NaV6O 15 @PPy nanofiber / TPU film and its preparation method and application.

[0049] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0050] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0051] Example 1

[0052] A V2O5@NaV6O 15 The preparation method of @PPy nanofiber / TPU film specifically comprises the following steps:

[0053] 0.7280g V2O5 and 0.5697g NaCl were dissolved in 85mL deionized water and stirred magnetically at 75℃ for 24min to form a suspension precursor. The precursor solution was subjected to chemical oxidation polymerization reaction with 0.694mL Py monomer at 0℃ for 12h. The obtained product was filtered and dried in an oven at 60℃ for 12h to obtain V2O5@NaV6O 15 @PPy nanofiber thermal conductive filler.

[0054] 5 g of TPU particles were mixed and dissolved with 40 mL of 1,4-dioxane solution at 75 °C to obtain solution A. 15@PPy thermal conductive filler was added to the dissolving solution A at a filling ratio of 1% to TPU, ultrasonically dispersed for 30 minutes, and vigorously stirred for 3 hours to obtain a thermal conductive and wave-absorbing slurry; then, the slurry was poured into a mold, and vacuumed at room temperature to remove bubbles; the slurry after the bubbles were removed was placed in an oven at 60°C to evaporate the solvent for 12 hours to obtain a thermal conductive and wave-absorbing multifunctional TPU composite film.

[0055] Figure 1 to Figure 3 They are respectively the phase and morphology of the product obtained in Example 1 of the present invention measured under XRD, EDX and scanning electron microscope.

[0056] From the above analysis, it can be seen that the product is V2O5@NaV6O 15 @PPy nanofibers, with a fiber length of 80.21 μm and a diameter of 163.7 nm.

[0057] The thermal conductivity properties are shown in Table 1. 15 @PPy nanofibers have excellent thermal conductivity with a thermal conductivity of 2.89W / (m·K).

[0058] The mechanical and wetting properties are shown in Table 2. The tensile stress of the TPU composite film is measured to be 30.825 MPa, and the tensile strain is 932.388%, which indicates that the TPU composite film has high strength and high elasticity. The measured water contact angle is 94.601°, and the rolling angle is 8°, which indicates that the TPU composite film has good hydrophobic and self-cleaning properties and can be used in rainy days and humid environments.

[0059] Example 2

[0060] A V2O5@NaV6O 15 @PPy nanofiber / TPU film preparation method, other conditions remain unchanged, based on Example 1, change V2O5@NaV6O 15 @The filling ratio of PPy thermal conductive filler to TPU is 5%.

[0061] The thermal conductivity and microwave absorption properties are shown in Table 1. 15 @PPy nanofibers have excellent thermal conductivity, with a thermal conductivity of 3.41W / (m·K). The maximum effective bandwidth with a reflectivity of less than or equal to -10dB is 8.32GHz, the maximum absorption is -22.3dB, the thickness is 2.8mm, and the thermal conductivity is 3.56W / (m·K).

[0062] The mechanical and wetting properties are shown in Table 2. The tensile stress of the TPU composite film was measured to be 26.29 MPa, and the tensile strain was 995.296%, which indicates that the TPU composite film has high strength and high elasticity. The measured water contact angle was 102.65°, and the rolling angle was 5°, which indicates that the TPU composite film has good hydrophobic and self-cleaning properties and can be used in rainy days and humid environments.

[0063] Example 3

[0064] A V2O5@NaV6O 15 @PPy nanofiber / TPU film preparation method, other conditions remain unchanged, based on Example 1, change V2O5@NaV6O 15 @The filling ratio of PPy thermal conductive filler to TPU is 7%.

[0065] The thermal conductivity and microwave absorption properties are shown in Table 1. 15 @PPy nanofibers have excellent microwave absorption and thermal conductivity properties, with a maximum effective bandwidth of 8.32 GHz for a reflectivity of less than or equal to -10 dB, a maximum absorption of -22.3 dB, a thickness of 2.8 mm, and a thermal conductivity of 3.56 W / (m·K).

[0066] The mechanical and wetting properties are shown in Table 2. The tensile stress of the TPU composite film was measured to be 22.635 MPa, and the tensile strain was 866.905%, which indicates that the TPU composite film has high strength and high elasticity. The measured water contact angle was 106.092°, and the rolling angle was 5°, which indicates that the TPU composite film has good hydrophobic and self-cleaning properties and can be used in rainy days and humid environments.

[0067] Example 4

[0068] A V2O5@NaV6O 15 @The preparation method of PPy nanofiber / TPU membrane, other conditions remain unchanged, and the volume of Py monomer added is changed to 1.388 mL based on Example 3.

[0069] The phase, composition and morphology of the obtained products measured by XRD, EDX and scanning electron microscope are as follows: Figures 4 to 6 As shown. From the above analysis, it can be seen that the product is V2O5@NaV6O 15 @PPy nanofibers, with a length of 38.06 μm and a diameter of 171.4 nm.

[0070] The thermal conductivity and microwave absorption properties are shown in Table 1. 15@PPy nanofibers have excellent microwave absorption and thermal conductivity properties, with a maximum effective bandwidth of 7.12 GHz for a reflectivity of less than or equal to -10 dB, a maximum absorption of -27.8 dB, a thickness of 2.4 mm, and a thermal conductivity of 3.48 W / (m·K).

[0071] The mechanical and wetting properties are shown in Table 2. The tensile stress of the TPU composite film was measured to be 24.58 MPa, and the tensile strain was 907.84%, which indicates that the TPU composite film has high strength and high elasticity. The measured water contact angle was 107.226°, and the rolling angle was 5°, which indicates that the TPU composite film has good hydrophobic and self-cleaning properties and can be used in rainy days and humid environments.

[0072] Example 5

[0073] A V2O5@NaV6O 15 @The preparation method of PPy nanofiber / TPU membrane, other conditions remain unchanged, and the volume of Py monomer added is changed to 2.776 mL based on Example 3.

[0074] The phase, composition, morphology and reflection loss curve of the obtained product measured by XRD, EDX and scanning electron microscope are shown in Figures 7 to 9 As shown. From the above analysis, it can be seen that the product is V2O5@NaV6O 15 @PPy nanofibers, fiber length is 29.35μm and diameter is 226.5nm.

[0075] The thermal conductivity and microwave absorption properties are shown in Table 1. 15 @PPy nanofibers have excellent microwave absorption and thermal conductivity properties, with a maximum effective bandwidth of 7.52 GHz for a reflectivity of less than or equal to -10 dB, a maximum absorption of -40.2 dB, a thickness of 2.8 mm, and a thermal conductivity of 3.25 W / (m·K).

[0076] The mechanical and wetting properties are shown in Table 2. The tensile stress of the TPU composite film was measured to be 23.75 MPa, and the tensile strain was 892.181%, which indicates that the TPU composite film has high strength and high elasticity. The measured water contact angle was 107.147°, and the rolling angle was 5°, which indicates that the TPU composite film has good hydrophobic and self-cleaning properties and can be used in rainy days and humid environments.

[0077] Example 6

[0078] A V2O5@NaV6O 15 The preparation method of the nanofiber / TPU membrane, other conditions remain unchanged, and the volume of the added Py monomer is changed to 0 mL based on Example 1.

[0079] The phase, composition, morphology and reflection loss curve of the obtained product measured by XRD, EDX and scanning electron microscope are shown in Figures 10-12 As shown. From the above analysis, it can be seen that the product is V2O5@NaV6O 15 Nanofibers with a fiber length of 22.8 μm and a diameter of 163.7 nm.

[0080] The thermal conductivity and microwave absorption properties are shown in Table 1. 15 The y nanofiber has excellent microwave absorption and thermal conductivity properties, with a maximum effective bandwidth of 9.84 GHz for a reflectivity of less than or equal to -10 dB, a maximum absorption of -40.2 dB, a thickness of 2.9 mm, and a thermal conductivity of 2.69 W / (m·K).

[0081] The mechanical and wetting properties are shown in Table 2. The tensile stress of the TPU composite film was measured to be 22.15 MPa, and the tensile strain was 993.224%, which indicates that the TPU composite film has high strength and high elasticity. The measured water contact angle was 105.086°, and the rolling angle was 6°, which indicates that the TPU composite film has good hydrophobic and self-cleaning properties and can be used in rainy days and humid environments.

[0082] Table 1 Wave absorption properties and thermal conductivity of the products obtained in Examples 1 to 6 of the present invention

[0083]

[0084] Table 2 Mechanical properties and wetting characteristics of the products obtained in Examples 1 to 6 of the present invention

[0085]

[0086] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A self-cleaning, high-strength, heat-conducting and wave-absorbing multifunctional TPU composite film, characterized in that: The multifunctional TPU composite film is V2O5@NaV6O 15 @PPy nanofiber / TPU film is prepared by dispersing a heat-conducting and wave-absorbing multifunctional filler and a thermoplastic polyurethane elastomer (TPU) matrix into an organic solvent in a certain proportion, and forming a film by evaporating the solvent; the heat-conducting and wave-absorbing multifunctional filler is V2O5@NaV6O 15 @PPy nanofibers have a one-dimensional core-shell structure with a length of 23 to 80 μm and a diameter of 48.7 to 265.9 nm; and the mass percentage of the thermal conductive and wave absorbing multifunctional filler in the TPU matrix is ​​1 to 7%.

2. A method for preparing the self-cleaning, high-strength, heat-conducting and wave-absorbing multifunctional TPU composite film as claimed in claim 1, characterized in that: The multifunctional TPU composite film is prepared by evaporating solvent to form a film, which specifically includes the following steps: (1) Add a certain amount of TPU particles to an organic solvent under an oil bath condition of 75-85°C and stir for 3-6 hours to obtain solution A; (2) The thermal conductive and wave absorbing multifunctional filler (V2O5@NaV6O 15 @PPy nanofibers) are added to the solution A in step (1) in a certain proportion, ultrasonically dispersed for 10 to 30 minutes, and vigorously stirred for 3 to 4 hours to obtain a thermal conductive and wave absorbing slurry; (3) pouring the thermal conductive and microwave absorbing slurry described in step (2) into a mold, evacuating the mold at room temperature, and removing bubbles for 3 to 5 minutes; (4) placing the mold after removing the bubbles in step (3) in a 60° C. oven to evaporate the solvent for 10 to 20 hours to obtain the self-cleaning, high-strength, thermally conductive and wave-absorbing multifunctional TPU composite film.

3. The method for preparing the self-cleaning, high-strength, heat-conducting and wave-absorbing multifunctional TPU composite film according to claim 2, characterized in that: The solvent in step (1) is 1,4-dioxane, and the concentration of TPU is 0.083-0.125 g / mL.

4. The method for preparing the self-cleaning, high-strength, heat-conducting and wave-absorbing multifunctional TPU composite film according to claim 2, characterized in that: In the step (2), V2O5@NaV6O 15 @The mass percentage of PPy nanofibers in the TUP matrix is ​​1-7%.

5. The method for preparing the self-cleaning, high-strength, heat-conducting and wave-absorbing multifunctional TPU composite film according to claim 2, characterized in that: The heat-conducting and wave-absorbing multifunctional filler is prepared by a liquid phase dissolution-recrystallization-redox polymerization process, which specifically includes the following steps: (1) V2O5 powder and NaCl were dissolved in deionized water and magnetically stirred at 75 °C for 24 h to form V2O5@NaV6O by liquid phase dissolution-recrystallization. 15 Nanofiber suspension; (2) Add the Py monomer to the V2O5@NaV6O in step (1) under stirring in an ice bath at 0-3°C. 15 The nanofiber suspension was stirred for 15 min and then placed in an ice bath at 0-3 °C for 12 h; (3) The product of step (2) was filtered and washed, and then dried in an oven at 60° C. to obtain the V2O5@NaV6O 15 @PPy nanofiber.

6. The method for preparing the self-cleaning, high-strength, heat-conducting and wave-absorbing multifunctional TPU composite film according to claim 5, characterized in that: In the step (1), the mass ratio of V2O5, NaCl and deionized water is 0.009:0.007:

1.

7. The method for preparing the self-cleaning, high-strength, heat-conducting and wave-absorbing multifunctional TPU composite film according to claim 5, characterized in that: In the step (2), Py and V2O5@NaV6O 15 The molar ratio is 5 to 15:

1.

8. An application of the self-cleaning, high-strength, heat-conducting-wave-absorbing multifunctional TPU composite film as claimed in claim 1 or the self-cleaning, high-strength, heat-conducting-wave-absorbing multifunctional TPU composite film prepared by the method as claimed in claim 2 in the field of microwave absorption and heat conduction.

Citation Information

Patent Citations

  • A thermal conductive and wave absorbing integrated flexible material and its preparation method and application

    CN115246994B

  • Preparation method of heat-conducting wave-absorbing powder and heat-conducting wave-absorbing sheet

    CN118027667A